Exploring the Role of Exosomes in Accelerating Orthodontic Tooth Movement - Abdalwhab Zwiri; Mohammad Khursheed Alam; Mohammad Younis Hajeer; Ebtehal Dhyab M. Alserhani; Dalia Abdulrahman Alanazi; Jinan Mohammed Alanazi; Nor Farid Bin Mohd Noor; Zafrina Islam (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Alveolar bone remodeling is a complicated biological process that is involved in orthodontic tooth movement (OTM). Recent studies have shown how exosomes, which are cell-secreted nanovesicles, influence cellular communication and encourage bone remodeling. Materials and Methods: Twenty Wistar rats were used in a prospective experimental investigation and split into two groups: one received exosome-enriched medium as an experimental treatment, and the other was a control group. The maxillary first molars were subjected to 10 g of force for 21 days to induce orthodontic tooth movement. The control group was given saline, whereas the experimental group was given injections of exosome-enriched media around the periodontal ligament every two weeks. Bone remodeling and root resorption were measured using histological examination and micro-CT analysis. ELISA and TRAP staining were used to measure arbitrary indicators of osteoclast activity and inflammation, respectively. Results: The OTM distance of the experimental group was significantly greater (1.5 ± 0.2 mm) than that of the control group (0.9 ± 0.1 mm; P < 0.05). The experimental group had 30% more osteoclasts, indicating increased alveolar bone resorption, according to micro-CT analysis. Histological analysis revealed that the group treated with exosomes had less inflammation and root resorption. Furthermore, ELISA verified that the experimental group had lower OPG levels and higher RANKL levels, suggesting faster bone remodeling. Conclusion: By encouraging alveolar bone remodeling and lowering inflammation, exosomes greatly improve orthodontic tooth mobility. According to these results, exosome-based treatments may be a viable additional treatment option to improve clinical results and hasten orthodontic tooth movement.